2020
DOI: 10.5751/ace-01477-150106
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behavior of the Eurasian Three-toed Woodpecker (Picoides tridactylus) and its implications for ecological restoration and sustainable boreal forest management

Abstract: Versluijs, M., S. Eggers, G. Mikusiński, J.-M. Roberge, and J. Hjältén. 2020. Foraging behavior of the Eurasian Three-toed Woodpecker (Picoides tridactylus) and its implications for ecological restoration and sustainable boreal forest management. Avian Conservation and Ecology 15(1):6. https:// ABSTRACT. Several studies have shown that the Three-toed Woodpecker (Picoides tridactylus) is strongly favored by large-scale disturbances, including forest fires. However, natural disturbances have largely disappeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
5
9
0
Order By: Relevance
“…Our results stress that important foraging substrates are spruce, dead trees, as well as trees with a DBH larger than 25 cm. The preference of Norway Spruce as foraging substrate in forests dominated by Scots Pine is in line with other studies showing that Spruce is the preferred tree species (Fayt 1999, Zhu et al 2012, Versluijs et al 2020). However, though Pines were selected less than based on their availability, the time Three-toed Woodpeckers foraged on Pine trees during observation sessions was found to be higher than for birch and Spruce (Figure 5A).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results stress that important foraging substrates are spruce, dead trees, as well as trees with a DBH larger than 25 cm. The preference of Norway Spruce as foraging substrate in forests dominated by Scots Pine is in line with other studies showing that Spruce is the preferred tree species (Fayt 1999, Zhu et al 2012, Versluijs et al 2020). However, though Pines were selected less than based on their availability, the time Three-toed Woodpeckers foraged on Pine trees during observation sessions was found to be higher than for birch and Spruce (Figure 5A).…”
Section: Discussionsupporting
confidence: 90%
“…However, our observation period (April until the end of June) overlaps with the pre-nesting period. It also overlaps with the observation periods used in Versluijs et al (2020) and Pakkala et al (2018a). In those studies, it was shown that Three-toed Woodpeckers use up to 14.7% of their foraging time in forests being subject to prescribed burnings (Versluijs et al 2020) and between 18-33% in mature forests (Pakkala et al 2018a, Versluijs et al 2020 for sap-feeding.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations